Network Building and Potential Development for Cashew Nut Online Business Entrepreneurs in Communities along the Lamsebok Economic Geography Route, Ubon Ratchathani Province - Srimaitree, Malinee; Thanisphong, Krittayamon; Kuuttha, Woranuch (Local Administration Journal, 2024)
The objectives of this research were: 1) to study the general conditions and potential of the cashew nut community along the Lamsebok economic geography route, 2) to examine the network building among the Lamsebok cashew nut community in Ubon Ratchathani Province, 3) to develop the community's potential to become online entrepreneurs in the Lamsebok cashew nut business, and 4) to evaluate participation and summarize lessons learned from network building and potential development in becoming entrepreneurs. A mixed-methods research approach was employed, with the quantitative research utilizing a survey questionnaire administered to a sample of 81 respondents. Quantitative data analysis involved the use of descriptive statistics, including frequencies, percentages, means, and standard deviations. For the qualitative research component, interviews and focus group discussions were conducted with 14 key informants, and the data were analyzed through content analysis. The findings were as follows 1) The study revealed the community’s living conditions related to the production, processing, and distribution of cashew nuts, which included the community group’s status, operational conditions, challenges, and an analysis of the environment and community potential. This process enhanced the community’s self-awareness, understanding of their environment, and appreciation of the community’s value. 2) The network of the Lamsebok cashew nut community was built through four processes: stimulating group consciousness, analyzing the network's status, formulating strategies, and implementation. 3) The community's potential was developed to become online entrepreneurs in the Lamsebok cashew nut business, which involved two main factors: internal and external. 4) The overall evaluation of network member participation indicated a moderate level of involvement. The lessons learned from network building and potential development revealed challenges and approaches to development, divided into three stages: preparation, establishment, and network operation, as well as the key factors contributing to the network's success.